The Effectiveness of Problem-Based Learning on Ecosystem Content toward Critical Thinking in Terms of Students' Metacognitive Awareness - Wiono, Wisnu Juli; Siregar, Yessica Solafide (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
This research aims to determine the effect of applying the PBL model on students' critical thinking abilities and to describe students' critical thinking abilities on the interaction of living things and their environment in terms of metacognitive awareness. The design in this research is a quasi-experiment using the Pretest-Posttest Control Group Design technique. Samples were taken using purposive sampling technique. Metacognitive awareness data was obtained through the Metacognitive Awareness Inventory (MAI) questionnaire which was analyzed descriptively. The population of this research was class VII students at SMPN 43 Bandar Lampung with a sample of 27 class VII 1 students as the experimental class and 25 class VII 2 students as the control class. The average N-Gain value for the experimental class was 0.65, the